Handbook of FPGA Design Security - Huffmire, Ted.; Irvine, Cynthia; Nguyen, Thuy D.; Levin, Timothy; Kastner, Ryan.; Sherwood, Timothy; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The purpose of Handbook of FPGA Design Security is to provide a practical approach to managing security in FPGA designs for researchers and practitioners in the electronic design automation (EDA) and FPGA communities, including corporations, industrial and government research labs, and academics. Handbook of FPGA Design Security combines theoretical underpinnings with a practical design approach and worked examples for combating real world threats. To address the spectrum of lifecycle and operational threats against FPGA systems, a holistic view of FPGA security is presented, from formal top level specification to low level policy enforcement mechanisms. This perspective integrates recent advances in the fields of computer security theory, languages, compilers, and hardware. The net effect is a diverse set of static and runtime techniques that, working in cooperation, facilitate the composition of robust, dependable, and trustworthy systems using commodity components.
and Motivation -- High Assurance Software Lessons and Techniques -- Hardware Security Challenges -- FPGA Updates and Programmability -- Memory Protection on FPGAs -- Spatial Separation with Moats -- Putting It All Together: A Design Example -- Forward-Looking Problems.
Keywords: Engineering; Systems engineering; Engineering; Circuits and Systems